Cultural Impact on Adolescent Behavior Advancing Health, Gender: A Scoping Review - Dewi Purnamawati; Syamsulhuda Budi Musthofa; Farid Agushybana (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Sexual and reproductive health is critical to the 2030 Sustainable Development Goals (SDGs). Various factors contribute to premarital sexual behaviour among adolescents, with culture being a pervasive influence in many countries. Adolescents in mountain communities are particularly vulnerable to engaging in premarital sexual behaviour. Aims: This review aims to explore research findings related to the cultural factors influencing premarital sexual behaviour among adolescents in general and specifically in mountain communities, contributing to the achievement of the SDGs. Method: This study employs a scoping review methodology. Search terms used in the articles include MeSH terms ["Adolescent" or "Teen"], ["Cultural impact" or "Cultural Role"], ["Premarital sex" or "Premarital sexual intercourses"], and ["Highland Communities" or "Mountain Communities"]. Databases utilised for article search include Science Direct, Proquest, and PubMed. Five journals published between 2019 and 2023 that meet the inclusion criteria were selected. Results: This review synthesises findings from 5 articles, narrowed down from an initial pool of 10,923 articles. All selected papers employ quantitative methods and originate from Ethiopia (3 articles), Nepal, and Tanzania. Conclusion: The review highlights the social, economic, and environmental influences on mountain communities, emphasising the cultural roles of alcohol consumption, social norms (customs), and family culture in shaping premarital sexual behaviour among adolescents. Education on the consequences of adolescent sexual behaviour is crucial, especially in cultures that tolerate such behaviours.